Asymmetries In Vowel-Pair Frequencies And Height Harmony In Bantu - Nichols, Stephen (My University, 2021)
In this paper, I present an exploration of vowel-pair frequencies in the nouns of six five-vowel Bantu languages and discuss their relationship with those alternations seen in verbs due to height harmony. Of particular interest is the disparity in the frequencies of two vowel pairs disagreeing in height, specifically [e.i] and [o.u], both between themselves and with the corresponding pairs which agree in height, namely [e.e] and [o.o]. The results show that while both [e.e] and [o.o] are over-represented, [e.i] and [o.u] are generally under-represented. In addition to this, [o.u] is consistently less frequent than [e.i] and the difference in representation between [o.o] and [o.u] is larger than between [e.e.] and [e.i].
Keywords: vowel-pair frequencies; HUMANITIES and RELIGION::Languages and linguistics::Other languages::Bantu languages; Asymmetries